2014
DOI: 10.1097/gme.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the first randomized sham-controlled trial of stellate ganglion block for hot flashes

Abstract: EDITORIALPerspectives on the first randomized sham-controlled trial of stellate ganglion block for hot flashes 788

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…11 An RCT of 187 symptomatic menopausal women found that clinical hypnosis was associated with a 74.2% reduction in hot flushes, compared with a 17.1% reduction in women randomized to structured attention control (P < 0.001). 12 The effectiveness of acupuncture, 13 exercise, 14 yoga, 15 paced respiration, 16 relaxation training, 17 and mindfulness-based stress reduction 18 has not been established.…”
Section: Vasomotor Symptomsmentioning
confidence: 99%
“…11 An RCT of 187 symptomatic menopausal women found that clinical hypnosis was associated with a 74.2% reduction in hot flushes, compared with a 17.1% reduction in women randomized to structured attention control (P < 0.001). 12 The effectiveness of acupuncture, 13 exercise, 14 yoga, 15 paced respiration, 16 relaxation training, 17 and mindfulness-based stress reduction 18 has not been established.…”
Section: Vasomotor Symptomsmentioning
confidence: 99%
“…The pathogenesis of chronic ulcerative colitis is complex. However, recent studies have shown that this disease and immune dysfunction are correlated[ 41 , 42 ], and that the stellate ganglion block technique plays a very important role in regulating immune function[ 43 - 46 ]. Therefore, the main aim of this study was to investigate the efficacy and safety of the stellate ganglion block technique in the treatment of chronic ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%